Factors Affecting HbA1c According to Sleep Duration in Adults with Diabetes - Myoungjin Kwon; Sun Ae Kim; Jiyoung Kim (Diabetology)
Background/Objectives: This study investigated factors affecting glycated hemoglobin (HbA1c) levels according to sleep duration in adults with diabetes. HbA1c is an important indicator for the diagnosis and management of diabetes, and lowering this value is important for reducing the risk of complications. Recent studies have shown that sleep duration and quality play important roles in controlling blood sugar levels in patients with diabetes. Therefore, we aimed to analyze the factors affecting HbA1c levels according to sleep duration in adult patients with diabetes and propose a personalized diabetes management strategy. Methods: This was a secondary analysis of data from the Korea National Health and Nutrition Examination Survey (KNHANES) conducted between 2022 and 2023. The study included 1363 adults aged ≥30 years who were diagnosed with diabetes by a doctor. The participants were categorized into three groups based on their sleep duration: <7 h, 7–9 h, and ≥9 h. Results: The significant factors affecting HbA1c levels varied according to sleep duration. Age, drinking, and stress were significant for those who slept for <7 h. For those sleeping 7–9 h, energy intake, protein intake, fat intake, and education level were significant. Health checkups and drinking were significant for those who slept for >9 h. Conclusions: This study suggests that sleep duration is an important variable in diabetes management and should be considered in personalized diabetes management strategies. Future studies should explore various factors related to sleep patterns in greater depth.